Knowledge of Artificial Fruit Ripening Among Consumers in Rivers State - Eze, Elizabeth E.; Asogwa, Emmanuel. U. (Advances in Social Sciences Research Journal, 2021)
The study investigated the knowledge of artificial fruit ripening among consumers in Rivers State. The study adopted a descriptive cross-sectional survey design. Four research questions and three null hypotheses tested at .05 alpha level guided the study. The population for the study was 2,617,600 respondents in fruit markets in Rivers State. A sample size of 1,024 fruit consumers was drawn suing multistage sampling procedure. Data were collected using a validated self-structured questionnaire titled "Knowledge of Artificial Fruit Ripening (KAFR)”. Guttman Split-Half Coefficient of 0.881 was obtained using Pearson Product Moment Correlation in conjunction with Spearman Brown correction statistics. Data were analyzed using percentage, mean, standard deviation, Chi-square, z-test, and One way Analysis of Variance. It was found that consumers had moderate knowledge of artificial fruit ripening in Rivers State. Also, male consumers, those within 31-40 years and those with tertiary education had higher knowledge of artificial fruit ripening. More so, the study revealed significant difference in knowledge among consumers in Rivers State based on gender, age and level of education. Based on the findings, the study recommended among others that; community health workers in Rivers State should organize regular heath education campaigns concerning the dangers of using chemicals for fruit ripening among consumers in Rivers State.